Alterrations in Neurotransmitter, Amino Acid and Free Radical Related Substances in Cerebrospinal Fluid in Patients with Cerebrovascular Diseases - Matsumiya, Teruhiko; Takada, Kaori; Takeda, Hiroshi; Egashira, Toru; Goto, Hiroshi (Nippon Ronen Igakkai Zasshi. Japanese Journal of Geriatrics, 1999)
Acetylcholinesterase (AChE), choline, monoamine and its metabolite, amino acid and superoxide dismutase (SOD) levels were measured in cerebrospinal fluid (CSF) in patients with cerebrovascular diseases. Patients were classified into the following four groups; controls: normal subjects without neurological disease, group A: cerebral hemorrhage, group B: cerebral infarction, group C: patients with mental impairment, including those in groups A and B, and a low score on Hasegawa's Dementia Rating Scale. CSF AChE level of groups A, B and C was decreased significantly, while choline concentration from patients showed a increase compared with that of control cases. CSF alanine concentration showed a tendency to increase, while glycine and glutamate tended to decrease. CSF epinephrine, norepinephrine or 3-methoxy-4-hydroxyphenylethylen glycol concentrations of groups A, B and C did not exhibit a significant difference from that in control cases. Some cases with cerebrovascular diseases showed low concentrations of both CSF 5-hydroxyindole acetic acid and homovanillic acid. However, dihydroxyphenyl acetic acid concentration was higher than in control cases. The CSF SOD level was not significantly from that in control cases. The changes in neurochemical substances in the CSF support their use as markers of cerebrovascular disease-related change.